Ciberadicción y rendimiento académico en estudiantes de grado 11 de una institución educativa del Distrito Especial, Turístico y Cultural de Riohacha (2022)
The purpose of this study was to analyze the effects of cyber addiction and academic performance in 11th grade students of the Divina Pastora Educational Institution of the Special, Tourist and Cultural District of Riohacha. For this, the types of cyber addiction were measured in relationship with the academic performance of the referenced students. The study corresponded to a non-experimental design with a cross-sectional correlational scope, with a sample of 55 participants. Statistical analysis was performed using the statistical program SPSS using the Spearman's Rho coefficient since the data found were abnormal, the main results being a significant negative correlation between online games and academic performance. Therefore, it is concluded that in general terms, students are not under effects relevant to the exposure of technologies.